NGOs hoping for a better, safer, worry free New Year - Kumar, Punitha; Kanyakumari, D. (New Straits Times, 2013)
EXPECTATIONS: Groups tell of what they're grateful for and what they're looking forward to in the future. THE slew of goodies rolled out by the government, in particular the 1Malaysia Housing Programme (PR1MA), was a resounding success, National House-buyers Association secretary-general Chang Kim Loong says.